P95 The effectiveness of varenicline versus nicotine replacement therapy for long term smoking cessation in primary care. (13th September 2016) - Taylor, GMJ; Taylor, AE; Thomas, KH; Martin, RM; Munafò, MR; Windmeijer, F; Davies, NM
Abstract : Background: Smoking is the leading preventable cause of death. A network meta-analysis of randomised trials has demonstrated that varenicline is the most efficacious treatment for short-term smoking cessation. However, there is no evidence of the relative effectiveness of varenicline versus nicotine replacement therapy (NRT) in general practice on long-term smoking cessation; or whether its effectiveness is modified by socioeconomic position (SEP). In this study we estimated the effectiveness of varenicline on smoking cessation using clinical data from primary care electronic medical records; and investigated if the effectiveness differed by SEP. Methods: Data were obtained from the Clinical Practice Research Datalink of electronic medical records (Trial Registration: NCT02681848 ). We conducted a prospective cohort study using electronic medical records of patients aged 18 years and over who were prescribed NRT (N = 149, 526) or varenicline (N = 70, 610) after September 1 st 2006. We compared the abstinence rates of patients prescribed varenicline to those prescribed NRT. We used three different analytic methods: Cox proportional hazards models, propensity score matched Cox models and instrumental variable analyses. Results: The Cox proportional hazards model indicated that patients prescribed varenicline were less likely to relapse to smoking for up to four years compared to those prescribed NRT, the fully adjusted hazard ratio and 95% confidence interval were: 0.95 (0.94 to 0.96). Estimates from the propensity score matched and instrumental variable analyses supported estimates derived from the Cox hazards model. We found little evidence that the effectiveness of varenicline differed by SEP. However, people from areas of lower deprivation were less likely to be prescribed varenicline. Discussion: Our results were consistent with the results from a network meta-analysis of RCTs. We add important evidence about the effectiveness of varenicline for long-term smoking cessation in primary care. Conclusion: Our results suggest that varenicline is more effective than nicotine replacement therapy for smoking cessation in primary care, and that its effectiveness does not vary by socioeconomic position.